Determinants of foreign direct investment in Iran: assessing the standard factors - M , Moniruzzaman; Kazi, Masuma Khatun; Atiyat, Hala Mohammad; Mahmood , Rana (Inderscience Publishers, UK, 2014)
This paper examines the determinants of foreign direct investment(FDI) of the Islamic Republic of Iran based on those of Malaysia that have been successful in attracting FDI since the early 1980s. The model adopted was based on a previous study on FDI determinants in Malaysia. Results of multiple regression analysis to determine whether FDI determinants in Iran are of the same significance as they are for Malaysia showed that none of the determinants under the study (economic growth, growth of export, exchange rate and balance of payment), except for government expenditure, is significant in affecting the flow of FDI in the case of Iran. On the basis of these results, the conclusion is drawn that these typical determinants fail to reflect the case of Iran. The study argues that one needs to look at Iran from a different perspective of FDI as the country is an outlier in the global economy owing to international sanctions.